Hawsh al-Basha: The Royal Cemetery in Cairo - Kolkailah, Mai Mohamed (AUC Knowledge Fountain, 2021)
This thesis focuses on Hawsh al-Basha, the royal cemetery near the mausoleum of Imam al-Shafi‘i, which is arguably one of the most intriguing architectural moments in Ottoman Cairo. Firstly, the historiography of Hawsh al-Basha is examined carefully in order to situate the mausoleum temporally and geographically. Secondly, for a critical rewriting of the historical narrative, this study systematically cross-references contemporary sources with nineteenth-century travel accounts, among other material evidence, to effectively reconstruct the complicated building chronology of Hawsh al-Basha and reassess when the mausoleum was built. Then, the study surveys the various categories of ornamentation employed at the royal cemetery, focusing on two chief categories: inscriptions and floral elements. In the process of a one-to-one mapping of Hawsh al-Basha’s eclectic blend of appropriated decorative motifs to local, eastern, and western models of inspiration, the definition of what constituted the Ottoman stylistic tradition during the nineteenth century is revised and expanded. Last but not least, this study develops a comparative trajectory between the artistic miliues in the imperial state of Istanbul and the khedival province of Cairo in order to analyze the vectors of influence driving the eclectic tendencies of Hawsh al-Basha’s stylistic evolution in relation to the broader contextual frameworks of Ottoman urban structures and socio-political agendas. Be it a strategically synthetic achievement or an unresolved hybrid monstrosity, Hawsh al-Basha represents a manifestation of power, a moment of decisive visual transformation, and a memory of a modernizing social order.